Factors linked to dissatisfaction of habitability in residential units during COVID-19 confinement in Argentina - Alba Ramos Sanz (ESTOA: Revista de la Facultad de Arquitectura y Urbanismo de la Universidad de Cuenca, 2024)
The present work aims the association of factors linked to the habitability satisfaction of isolated and semi-detached residential units in apartment buildings is analyzed, during lockdown due to Covid-19 in Argentina. Using the snowball technique, an electronic survey is disseminated in the strictest lockdown moment, reaching a sample of 137 users of residential units. The answers for two research questions are empirically validated with inferential statistical techniques, giving rise to hypotheses born from the conflicting aspects detected in habitability satisfactions such as the availability of interior spaces, perceived natural lighting, as well as the age of the respondent, among others. Conclusions confirm the relevance of natural lighting could replace the demand for spatial amplitude, and its importance based on the users age range among other aspects of significant association. The results obtained serve as foundations for housing and territorial planning policies to mitigate habitability dissatisfaction risks during social confinement events.